The Role of Artificial Intelligence in Diviorce Proceedings in the Netherlands: A Legal Analysis Based on Islamic Legal Principles - Septia , Sya’baniatie Ninda (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
AI chatbots in divorce cases in the Netherlands offer efficiency but fall short in ensuring justice (al-‘adl), consultation (shura), and the protection of spousal rights in Islamic law. This study highlights the need for human involvement and adherence to shar‘i values to ensure divorce processes are not only legally valid but also substantively and ethically just.